Personal experience of a physician : with an appeal to the medical and clerical professions, and an appendix, a review of "Christ and the temperance question, " in the Christian union.: with an appeal to the medical and clerical professions, and an appendix, a review of "Christ and the temperance question, " in the Christian union. (2012) - Ellis, John, 1815-1896
No abstract available